Peran adverse childhood experience terhadap kecemasan sosial pada remaja - Rayssa Giovan Azaria; Nandy Agustin Syakarofath (Universitas Muhammadiyah Malang, 2024)
Social anxiety phenomena can occur easily because each individual has a tendency to experience social anxieties with their individual's different levels of anguish. An adverse childhood experience (ACE) is a negative experience that a person experiences during childhood, such as physical violence, sexual violence, neglect, or emotional instability in the family. Some literature shows that person with more ACE experience tend to have a higher level of social anxiety compared to those who do not experience ACE. The aim of this survey is to find out the impact between adverse childhood experience and social anxiety in adolescents. This research used quantitative approach with a correlational design. The subjects were determined using random sampling techniques with samples of 282 students. As for the ACE variable, the World Health Organization Adverse Childhood Questionnaire (WHO ACE-IQ) scale and the social anxiety variable using the SAS-A scale (Social Anxiety Scale for Adolescents). The analysis of the research data uses simple linear regression analysis. The results of this study show that there is no correlation between adverse childhood experience and social anxiety. Adverse childhood experience does not have significant influence with social anxiety in adolescents.